Robust and durable response to first-line treatment of pembrolizumab combined with chemotherapy in two patients with metastatic thymic squamous cell carcinoma: Case report - Chen, Cui; Sun, Peng; Long, Jianting (Frontiers in Immunology, 2022)
Thymic carcinoma is a rare and aggressive disease with poor outcome. There is no established treatment regimen for late-stage thymic carcinoma. While the efficacy of checkpoint inhibitor was proved to be promising, as single agent, in patients with refractory/recurrent thymic carcinoma which progressed after chemotherapy, the efficacy and safety of combination of ICIs and chemotherapy as front-line treatment in metastatic thymic carcinoma have not been explored yet. Herein, we report the first two cases of metastatic thymic squamous cell carcinoma receiving the combined approaches of pembrolizumab and chemotherapy as first-line treatment. Of the two patients, one had a complete radiological response of mediastinal masses with sustained remission over 3 years, another one with widespread disease had a good partial response over 20 months and achieved no evidence of disease radiologically after undergoing percutaneous radiofrequency ablation for residual liver metastases. NGS showed low tumor mutation burden and MSS in both patients. Immunohistochemistry analysis of the tumor showed high PD-L1 expression in patient 1 and low PD-L1 expression in patient 2. Pembrolizumab combined with chemotherapy may be an attractive strategy for the first-line treatment of metastatic thymic carcinoma and thus warrants further evaluation.